IoT based Smart Poultry Management System - C, Karun K; Subedi, Karan; Sharma, Siddharth; Paneru, Pradip (Journal of ISMAC, 2024)
This research focuses on the development of an intelligent system utilizing embedded frameworks and smartphone technology for monitoring and managing chicken farms. The proposed system aims to control environmental parameters and automate feeding and water supply, offering a cost-effective, asset-saving, and quality-oriented approach to poultry farming. By leveraging smart devices and IoT technologies, this system can replace manual labour, addressing industry labour challenges and introducing semi-automation. The system encompasses tasks such as feeding using a container, water supply through nipple waterers, temperature and humidity regulation with fans and heaters, automatic lighting, and real-time environmental monitoring accessible through IoT cloud data. This technology-driven solution holds promise for enhancing productivity and efficiency in poultry farming and broader agricultural applications.
Keywords: Poultry; Temperature; Humidity; Automation; Feeding; Water Supply; Automatic Lighting; IoT